Hands-On Microservices with Spring Boot and Spring Cloud : Build and Deploy Java Microservices Using Spring Cloud, Istio, and Kubernetes. - Larsson, Magnus (Packt Publishing, Limited, 2019)
The goal of the book is to demonstrate how to use essential parts of Spring Boot and Spring Cloud to develop production ready microservices. You will also learn how to deploy the microservice to Kubernetes, use Istio as a service mesh and finally learn how to use their features to provide scalability, robustness, observability and manageability.